The neuro-immune axis in cancer: mechanisms of innervation-driven tumor progression and therapeutic opportunities - Zhang, Liang; Zhu, Dantong; Wang, Junyi; Guo, Jiyang; Jiang, Mingzhe; Qi, Xinhui; Zhang, Zhuo; Zheng, Zhendong (Frontiers in Immunology, 2026)
Innervation plays a key role in tumor progression, and malignant tumor cells often invade peripheral nerve or the central nervous system, significantly altering tumor biological function. In this review, the multi-dimensional role of innervation in cancer biology is comprehensively discussed, the molecular mechanisms involved and their effects on the tumor microenvironment are deeply analyzed, and therapeutic strategies are proposed. We systematically summarize the interactions between cancer cells and neural tissue, focusing on how key signaling pathways regulate the core elements of this process. The analysis focused on the pathological features of innervation in specific cancer types, particularly breast, pancreatic, and prostate cancers, revealing the unique mode of action of innervation in these cancers. In addition, we explored the combined effects of innervation on the tumor microenvironment, including immune cell infiltration, angiogenesis, metabolic reprogramming, and the development of cancer-related pain. Together, these changes promote tumor growth and spread, further highlighting the importance of innervation in tumor progression. Finally, this review proposes the potential therapeutic value of innervation in the treatment of cancer, and aims to promote the development of the field of innervation research. A deeper understanding of the complex relationship between innervation and cancer progression is critical to optimizing treatment strategies, improving patient outcomes, and expanding the boundaries of our understanding of cancer biology.